Oxidative Stress and Proteostasis Network: Culprit and Casualty of Alzheimer's-Like Neurodegeneration. (8th July 2014) - Di Domenico, Fabio; Head, Elizabeth; Butterfield, D. Allan; Perluigi, Marzia
Abstract : Free radical-mediated damage to proteins is particularly important in aging and age-related neurodegenerative diseases, because in the majority of cases it is a non-reversible phenomenon that requires clearance systems for removal. Major consequences of protein oxidation are loss of protein function and the formation of large protein aggregates, which are often toxic to cells if allowed to accumulate. Deposition of aggregated, misfolded, and oxidized proteins may also result from the impairment of protein quality control (PQC) system, including protein unfolded response, proteasome, and autophagy. Perturbations of such components of the proteostasis network that provides a critical protective role against stress conditions are emerging as relevant factor in triggering neuronal death. In this outlook paper, we discuss the role of protein oxidation as a major contributing factor for the impairment of the PQC regulating protein folding, surveillance, and degradation. Recent studies from our group and from others aim to better understand the link between Down syndrome and Alzheimer's disease neuropathology. We propose oxidative stress and alteration of proteostasis network as a possible unifying mechanism triggering neurodegeneration.